Surgical anatomy of the submental artery perforator flap and assessment for application in postoperative reconstruction following oral cancer surgery: a prospective clinical study. Issue 7 (July 2021) - Bin, X.; Wu, X.; Huang, L.; Zhou, Y.; Guo, F.
Abstract: The submental artery perforator flap (SMAPF) has an elongated pedicle, allowing good cosmetic outcomes to be achieved following oral reconstruction surgery. The improper dissection of perforators often leads to a vascular flap crisis. To avoid this, some surgeons choose to carry amounts of connective tissue around the pedicle. However the inclusion of connective tissue on the pedicle raises concerns about oncological safety. A surgical anatomical study of the submental vessel patterns and subdivisions of the cervical level I lymph nodes was conducted on 33 patients with primary oral cancer who underwent reconstruction with a SMAPF after tumour resection. The variations in vessels and cervical level I lymph nodes observed during SMAPF harvesting were recorded and analyzed. Two patterns of submental artery perforators and three patterns of submental veins were identified. The different characteristics of the lymph node distribution were elucidated for five subdivisions. All SMAPFs survived ( n = 33, 100%); however, two SMAPFs exhibited partial losses. The 3-year survival rate of patients was 84.5 ± 6.4%, and there were no suspected flap-related recurrences. With detailed anatomical information on the vascular system and lymph node subdivision, SMAPFs are a reliable choice for postoperative reconstruction following oral cancer surgery, meeting the standards for oncological safety.